2020
DOI: 10.1029/2019wr025614
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for Adaptive Water Supply Management When Quantifying Climate and Land Cover Change Vulnerability

Abstract: Climate and land cover change strongly shape water resources management, but understanding their joint impacts is extremely challenging. Consequently, there is limited research of their integrated effects on water supply systems, and even fewer studies that rigorously account for infrastructure investment and management interventions. We utilize ecohydrologic modeling to generate watershed outflows under scenarios of climate and land cover change, which in turn drive modeled water utility-level decision making… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 87 publications
(128 reference statements)
0
11
0
1
Order By: Relevance
“…A distributional approach addresses these questions by generating multiple, equally plausible realizations as a foundation for hypothesis testing. Accordingly, our seeding algorithm makes simplifying assumptions (e.g., a basic probability model generated from a short list of common, spatially explicit drivers of change, such as elevation and slope) in exchange for the greater computational efficiency to produce libraries of rasters at the finer scales (e.g., 30–90 meters) needed for many ecological service and indicator analyses (e.g., [ 6 , 12 – 14 , 54 ]).…”
Section: Discussionmentioning
confidence: 99%
“…A distributional approach addresses these questions by generating multiple, equally plausible realizations as a foundation for hypothesis testing. Accordingly, our seeding algorithm makes simplifying assumptions (e.g., a basic probability model generated from a short list of common, spatially explicit drivers of change, such as elevation and slope) in exchange for the greater computational efficiency to produce libraries of rasters at the finer scales (e.g., 30–90 meters) needed for many ecological service and indicator analyses (e.g., [ 6 , 12 – 14 , 54 ]).…”
Section: Discussionmentioning
confidence: 99%
“…2 Normalized score using equation (1), dimensionless. 3 IQR is interquartile range. 4 Reach 1 is a losing reach and seepage is simulated; Reach 5 is a gaining reach without simulated seepage.…”
Section: Climate Change (Cc) Scenariomentioning
confidence: 99%
“…Climate and LULC changes are expected to have interactive impacts on water availability [2,3]. Many studies have examined the impacts of climate and LULC changes on ecosystem health, streamflow, or water availability [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. In these studies, future climate trends are incorporated using simulated weather from downscaled global climate models (GCMs) or regional climate models (RCMs) driven by one or more emissions scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…It is prominent that RHESSys has a hierarchical structure ( Figure 2) to better reflect the multi-scale characteristics of ecohydrological processes in a watershed while other ecohydrological models have 'basin-grid' and 'basin-subbasin-grid' structures. For instance, Gorelick et al [17] found that RHESSys can handle mixed and heterogeneous land cover at a fine spatial resolution and is suitable for more detailed ecohydrological modeling in small catchments. However, SWAT (Soil and Water Assessment Tool) is spatially lumped at the subbasin level and applies to model large basins with spatially well-segregated landscapes.…”
Section: The Basic Structure and Development History Of Rhessysmentioning
confidence: 99%
“…However, RHESSys has a hierarchical structure that simulates various combinations of scenarios (e.g., climate, land use) at individual scales and thus is enabled to provide land management modeling and its far-reaching impacts on the local basins. Moreover, RHESSys is suitable for coupling with other models, which provides opportunities to study specific land-management measures, such as reservoir construction [6,9,17].…”
Section: Land Managementmentioning
confidence: 99%